2022-RA-438-ESGO A comparison of survival and recurrence pattern of patients presenting locally advanced cervical cancer according to the histological subtype: a monocentric retrospective study. (20th October 2022) - de Cuypere, Marjolein; Pleyers, Clémence; Hermesse, Johanne; Lovinfosse, Pierre; Delbecque, Katty; Gonne, Elodie; Kakkos, Athanasios; Goffin, Frédéric; Kridelka, Frédéric; Gennigens, Christine
Abstract : Introduction/Background: According to best practice, adeno-/adenosquamous cell (AC) and epidermoid cell (EC) locally advanced cervical cancers (LACC) are treated by chemoradiation ( CRT) followed by image-guided adapted brachytherapy (IGABT). However, literature shows different survival prognosis between these histological subtypes. In this retrospective monocentric study, we compared the prognosis and recurrence profile of patients presenting LACC with EC and AC histology. Methodology: Patients with LACC who underwent CRT followed by IGABT between 2010 and 2020 at the University Hospital of Liège were retrospectively included. Clinical features and the pattern of recurrence between the EC and AC groups were compared. Groups were compared by Student t- or Chi-square tests. Survival outcomes were evaluated by log-rank test. Results: Of the 211 patients, 181 (86%) and 30 (14%) presented EC and AC carcinoma, respectively. The AC group is younger (mean 49.5 versus 54.4 years; p= 0.043) whereas the EC group presented more positive pelvic lymph nodes on the pre-operative PET/CT (53% versus 30%, p =0.029). No statistically significant differences were observed for FIGO 2009 stage, tumour size, parametrial and vaginal invasion. The overall treatment duration was similar in both subgroups with a median of 50 days. The 5-year overall survival rates for the EC and AC groups were 70.4% and 63.1% ( p =0.17), respectively; the 5-year recurrence-free survival rates were 75, 8% and 61.6% ( p= 0.090), respectively. The proportion of patients with local, pelvic, para-aortic and distant recurrence was respectively in the EC and AC group: 5% versus 10% ( p= 0.38); 3% ( p =1.00); 9% versus 7% ( p =1.00) and 16% versus 17% ( p =0.79). Conclusion: The outcomes and recurrence profiles seem statistically equivalent between the EC and AC groups of patients with LACC treated by CRT and IGABT. However, in terms of absolute values, the AC group demonstrates worse prognosis and local control rates.